2007
DOI: 10.1021/ja075876l
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of Sagittamide A from Residual Dipolar Coupling Enhanced NMR

Abstract: Sagittamide A is a long-chain acyclic α,ω-dicarboxylic acid with eight stereocenters. The central hexahydroxyhexane moiety carries six of them. For this moiety, two different relative stereochemical assignments were published in 2006. In this communication, one relative configuration is clearly singled out based on NOEs, J- and residual dipolar couplings despite conformational averaging that is present in this moiety. The proposed NMR method relies on the measurement of dipolar couplings in recently introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
94
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 18 publications
3
94
0
1
Order By: Relevance
“…Although the absolute configuration at C4 and C5 could be derived from the trans-isoa-acid 3 a, the assignment of the neighboring CH 2 moieties in the inherently flexible five-membered rings could not be achieved unambiguously based on conventional scalar coupling analysis, thus leaving the configuration at C1', C2'', and C3' unidentified. To determine the relative chirality of these centers, a number of experiments were performed to measure residual dipolar couplings (RDCs), which recently enabled the successful prochiral assignment [30][31][32][33] and configurational analysis [34][35][36][37][38][39][40] of several organic compounds. Two samples of tricyclocohumol (4 a) were prepared; one was dissolved in [D 6 ]DMSO, and the other one was diffused into a poly(acrylonitrile)/ [D 6 ]DMSO gel, [41][42][43] which was then stretched using the method reported recently [44,45] to obtain partial alignment of the solute.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…Although the absolute configuration at C4 and C5 could be derived from the trans-isoa-acid 3 a, the assignment of the neighboring CH 2 moieties in the inherently flexible five-membered rings could not be achieved unambiguously based on conventional scalar coupling analysis, thus leaving the configuration at C1', C2'', and C3' unidentified. To determine the relative chirality of these centers, a number of experiments were performed to measure residual dipolar couplings (RDCs), which recently enabled the successful prochiral assignment [30][31][32][33] and configurational analysis [34][35][36][37][38][39][40] of several organic compounds. Two samples of tricyclocohumol (4 a) were prepared; one was dissolved in [D 6 ]DMSO, and the other one was diffused into a poly(acrylonitrile)/ [D 6 ]DMSO gel, [41][42][43] which was then stretched using the method reported recently [44,45] to obtain partial alignment of the solute.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…The technique involves two steps: residual dipolar coupling (RDC)-enhanced NMR spectroscopy to enable the determination of the conformational ensemble and the relative configuration; [11,12] and subsequent prediction of ORD spectra by DFT calculations to differentiate between enantiomers. Combined, the two steps reveal the absolute configuration of a flexible molecule in solution.…”
Section: Introductionmentioning
confidence: 99%
“…However, the calculated 15 Table 1). The Δδ( 15 N) of the nonprotonated model (254 ppm) indicated that the positive charge must be compensated.…”
mentioning
confidence: 99%